2012
DOI: 10.3329/jhpn.v29i6.9895
|View full text |Cite
|
Sign up to set email alerts
|

Antitubercular Drug Resistance in Four Healthcare Facilities in North India

Abstract: Tuberculosis (TB) is a major public-health problem in India, having the highest number of incident and multidrug-resistant (MDR) TB cases. The study was carried out to appraise the prevalence of first-line anti-TB drug resistance in Mycobacterium tuberculosis (MTB) and its patterns among different types of TB patients from different settings in a province of North India. Of 3,704 clinical specimens, 345 (9.3%) were culturepositive, and drug-susceptibility testing was carried out for 301 MTB strains. A high lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 20 publications
8
11
0
Order By: Relevance
“…The prevalence of rifampicin-resistant M. tuberculosis in this study was in keeping with previous studies in Nigeria [28], North India [29], Iran [30] and Northeast China [25]. However, it was higher than studies observed in Ethiopia [8, 9, 31, 32], Kenya [33], Nigeria [34], Uganda [35] and South of Iraq [36].…”
Section: Discussionsupporting
confidence: 89%
“…The prevalence of rifampicin-resistant M. tuberculosis in this study was in keeping with previous studies in Nigeria [28], North India [29], Iran [30] and Northeast China [25]. However, it was higher than studies observed in Ethiopia [8, 9, 31, 32], Kenya [33], Nigeria [34], Uganda [35] and South of Iraq [36].…”
Section: Discussionsupporting
confidence: 89%
“…According to our study, we found 132 (9.1%) of rifampicin-resistant cases among con rmed TB cases. This result is comparable with studies conducted in Debre Markos Referral Hospital (10.3%) [13], Felege Hiwot Referral Hospital and Debre Tabor Hospital (9.3%) [20], Addis Ababa (9.9 %) [48] and India (10.5%) [38].Our nds are higher than studies conducted on northwest, east and south parts of Ethiopia (2.9%-5.7%) [6,19,31-32,39,42,46 and 48], Nigeria (2.9%) [24] and Zambia (5.9%) [33].The possible explanation for these variations could be related to our retrospective approach spanning four years, or differences in study designs .However, our incidence was lower than for studies conducted in Gondar 15.8% [14],other parts of Ethiopia (11.5-39.4) [39-40and 51],Congo (42.2%) [47] and China (17.6-26.3%) [43 and 50].…”
Section: Discussionsupporting
confidence: 87%
“…treated PTB patients2238.120.2LJTertiary hospital16Mishra J K et al, 2009 [61]Varanasi2007–2009Combined PTB patients5121.626.511.8Not specifiedTertiary hospital17Porwal C et al, 2013 [28]Delhi2007–2010Prev. treated PTB patients60979.379.38.767.932.13.0MGIT 960Tertiary hospital18Sharma S K et al (c), 2011 [62]Delhi2008–2009Newly diagnosed PTB patients1771.71.11.1LJPrimary healthcare19Yadav R et al, 2013 [63]Chandigarh2008–2010Combined PTB patients17148.55.91.24.714.017.033.35.9LJTertiary hospital20Gupta A et al (a), 2011 [64]Varanasi2008–2010Combined PTB patients28857.635.8LJTertiary hospital21Sagar T et al, 2013 [65]Delhi2009–2010Combined PTB patients365.62.82.8LJTertiary hospital22Singh N et al, 2014 [66]Delhi2009–2012Pre...…”
Section: Resultsmentioning
confidence: 99%